2015
DOI: 10.1111/ped.12625
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and bed rest, even for a relatively short period, are risk factors for ceftriaxone‐associated pseudolitiasis

Abstract: Special attention should be paid to the degree of oral intake and patient activity when CTRX is prescribed. We recommend regular ultrasonographic follow up of patients receiving CTRX, to evaluate the formation of biliary pseudolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 14 publications
0
38
0
2
Order By: Relevance
“…Onset of pseudobiliary stones varies from 2 to 22 days after starting treatment with ceftriaxone [2], [4], [10], [11], [12]. Kimura reported that stones appeared on day 30 after the end of 12 days of ceftriaxone administration [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onset of pseudobiliary stones varies from 2 to 22 days after starting treatment with ceftriaxone [2], [4], [10], [11], [12]. Kimura reported that stones appeared on day 30 after the end of 12 days of ceftriaxone administration [5].…”
Section: Discussionmentioning
confidence: 99%
“…Kimura reported that stones appeared on day 30 after the end of 12 days of ceftriaxone administration [5]. Generally, spontaneous exclusion (or disappearance) of the stones occurs relatively quickly after stopping ceftriaxone administration, but the period varies from 2 days to 5 months after the discontinuation of ceftriaxone administration [3], [4], [5], [8], [10], [12], [13]. In an in vitro study, at doses of ceftriaxone greater than or equal to 2 g, precipitation of ceftriaxone could occur, and the development of ceftriaxone-induced biliary sludge could be because of poor solubility that occurs in patients receiving a high-dose treatment (greater than or equal to 2 g) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Результаты современных исследований показы-вают, что одним из побочных эффектов действия цефалоспоринов ІІІ поколения является нарушение однородности желчи [1,[6][7][8][9]. Данный феномен полу-чил название «цефалоспорининдуцированный били- арный псевдолитиаз» (ЦИБПЛ).…”
Section: Introductionunclassified
“…Установлено, что при билиарном сладже, индуцированном цефтриаксо-ном, основным компонентом осадка желчи является кальциевая соль цефтриаксона, а также в преципитате содержится небольшое количество гранул билирубина и кристаллов моногидрата холестерина [16]. В послед-ние годы проведен ряд исследований, определяющих дозы и длительность применения цефалоспоринов ІІІ поколения, при которых становится возможным фор-мирование билиарного сладжа [6][7][8][9]11].…”
Section: Introductionunclassified
“…A recent study suggested that a short period of fasting and bed rest are both associated with biliary pseudolithiasis. (5) Ensuring adequate hydration may help to reduce the occurrence of this side effect. The mean duration to resolution of biliary pseudolithiasis is about 15 days.…”
Section: E F T R I Axo N E -I N D U C E D P S E U D O L I T H I a Smentioning
confidence: 99%